Interim opioid agonist treatment for opioid addiction: a systematic review - Laura Samsó Jofra; Teresa Puig; Ivan Solà; Joan Trujols (BMC, 2022)
Abstract Background Opioid use disorder is a public health problem and treatment variability, coverage and accessibility poses some challenges. The study's objective is to review the impact of interim opioid agonist treatment (OAT), a short-term approach for patients awaiting standard OAT, in terms of treatment retention, access to standard OAT, quality of life and satisfaction with treatment. Method We conducted a systematic review searching MEDLINE, EMBASE, PsycINFO, and CENTRAL up to May 2020. Due to variability between studies and outcome measurements, we did not pool effect estimates and reported a narrative synthesis of findings rating their certainty according to GRADE. Results We identified 266 unique records and included five randomized trials with some limitations in risk of bias and one observational study limited by selection bias. The studies assessed similar approaches to interim OAT but were compared to three different control conditions. Four studies reported on treatment retention at 4 months or less with no significant differences between interim OAT and waiting list or standard OAT. Two studies reported treatment retention at 12 months with no differences between interim OAT and standard OAT. Two trials assessed access to standard OAT and showed significant differences between interim OAT and waiting list for standard OAT. We rated the quality of evidence for these outcomes as moderate due to the impact of risk of bias. Data on quality of life or satisfaction with treatment was suboptimal. Conclusions Interim OAT is likely more effective than a waiting list for standard OAT in access to treatment, and it is probably as effective as standard OAT regarding treatment retention. PROSPERO registration CRD42018116269.